Exercise Therapy as Therapeutic Option For Muscle Atrophy: Study on Signaling IGF-1 in Skeletal Muscle - Gifari, Muhammad Yusrin Al; Nafiah, N; Rahmani, R (Ikatan Fisioterapi Indonesia, 2022)
Background - Muscle wasting is caused by metabolic system disorders involving disorders of the musculoskeletal system, one of the risks is insulin growth factor (IGF1) damage. Exercise therapy is one of the physiotherapy interventions that can increase muscle mass and strength, reduce oxidative stress related to aging, chronic inflammation, increase autophagy, and improve mitochondrial function. Methods - The method used in this paper is a literature review using a search database of Google Scholar, Pubmed, and Researchgate with the topic search keywords